138k views
5 votes
Consider the composite function (g (x) ) = StartRoot StartFraction 1 Over x squared minus 3 EndFraction EndRoot. If g(x) = x2 – 3, what is f(x)?

f (x) = StartRoot StartFraction negative 1 Over x EndFraction EndRoot
f (x) = StartRoot StartFraction negative 1 Over x + 6 EndRoot EndFraction
f (x) = StartRoot StartFraction 1 Over x EndFraction EndRoot
f (x) = StartRoot StartFraction 1 Over x + 6 EndFraction EndRoot

User Mariola
by
5.8k points

1 Answer

0 votes

Answer:

answer is c

Explanation:

User Slashmili
by
4.5k points